Elderly intelligient care I - Tan, Siew Sia (2016)
The demands for elderly care have been on the rise with the rapid increase in ageing population. It is essential to develop intelligent elderly care to meet specific healthcare needs of individuals. This project aims to build a low cost and efficient monitoring system that leverages on the state-of–art technology in the indoor positioning system.